Nanostructured liquid crystalline formulation as a remarkable new drug delivery system of anti-epileptic drugs for treating children patients - Hadel Abo El-Enin; Areej Hamed AL-Shanbari (Elsevier, 2018)
Purpose: Development of a new dosage-form of antiepileptic-drugs appropriated for children. Methods: Clonazepam (Cl) was formulated as cubosomal-gel (cub-gel) to be used as a patch reservoir through transdermal-route. Cubosomes prepared using glycerol-mono-oleate(GMO)/Pluronic-F127(PF127) mixture. An actual-statistical design was used to investigate the effect of different stabilizing agents (Ethanol and PVA) and surfactant concentration on cubosomes' particle size and entrapping-efficiency. The selected formulae were evaluated by testing particle-morphology, in vitro drug release and stability. Cub-gel was prepared using selected cubosome formulae. The optimal cub-gel subjected to in vitro dissolution, ex-vivo permeation and skin deposition studies followed by studying its pharmacological effect. Results: Using PVA or Et as stabilizers with PF127 significantly decreases the average cubosomes'PS (352 ±  2.8 and 264 ± 2.16 nm) and increases EE (58.97 ± 4.57% and 54.21 ± 3.89%). Cubosomes increase the initial release rate of Cl to ensure rapid therapeutic effect (37.39% and 46.04% in the first hour) followed by a prolonged release till 4 h. Cub-gel containing PVA showed significantly higher Cl-transdermal permeation when compared to Cl-suspension. Moreover, increases the retention-time (89.57% at 48 h) and skin-deposition up to 6-times. It also reduces the epileptic seizures and alters the behavioral parameters induced by pilocarpine. Conclusions: Cubosomal-gel could be considered an innovative dosage-form for Cl through the transdermal route. Keywords: Epilepsy, Antiepileptic, Clonazepam, Cubosomes, Cubogels